Thermodynamic Study of Complex Formation Between Benzo-15-crown-5 and Phenylaza-15-crown-5 with La3+ Cation - Hossein Arbab Zavar, Mohammad; Heydari, Somayeh; Hossein Rounaghi, Gholam (Asian Journal of Chemistry, 2011)
The equilibrium constants and the thermodynamic parameters for complex formation of benzo- 15-crown-5 (B15C5) and phenylaza-15- crown-5 (PhA15C5) with La3+ cation have been determined by conductivity measurements in acetonitrile-dimethylformamide (AN/DMF), acetonitriledimethyl sulfoxide (AN/DMSO), acetonitrile-1,2-dichloroethane (AN/1,2DCE) and acetonitrilechloroform (AN/CHCl3) binary solutions. Phenylaza-15-crown-5 forms a 1:1 complex [M:L] with La3+ cation, but in the case of benzo-15-crown-5 ligand, a 1:2 [M:L2] complex is formed in some binary solutions. The stability of the complexes is sensitive to the solvent composition and a non-linear behaviour was observed for variation of log Kf of the 1:1 complexes versus the composition of the binary mixed solvents. The thermodynamic parameters (ΔH°c, ΔS°c) for formation of (B15C5.La)3+ and (PhA15C5.La)3+ complexes were obtained from temperature dependence of the stability constant using the Van't Hoff plots. The results show that in most of the cases, the complexes are both enthalpy and entropy stabilized. A non-linear behaviour was observed for changes of log Kf of the1:1 complexes versus the composition of the binary mixed solvents which was explained in terms of solvent-solvent interactions and also the heteroselective solvation of the species involved in the complexation reactions.